The strategy of enhancing article citation and H-index on SINTA to improve tertiary reputation - Untung Rahardja; Eka Purnama Harahap; Shylvia Ratna Dewi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Development of technology as it is today, most students or lecturers in education community write documents or articles digitally. However, there are still many obstacles when searching for a legitimate source of reference and to know whether it contains plagiarism or not. Until present, there are still many students and lecturers who seek references from sources that have not been valid and not yet trusted, but it is considered a fatal mistake for writing articles and also writing thesis or dissertation from untrusted resources. Therefore, Google Scholar system helps to alleviate this problem. Google also facilitates the use of citations or references. The purpose of this research is to identify the number of citation H-Index owned by lecturers at tertiary education and score ranking achieved at tertiary education SINTA (Science and Technology Index) Ristekdikti. Citing an article from another publication is one form of scientific communication by the author or researcher. The large number of citations obtained from an article published in the publication indicates how significant the contributions of the author in improving the quality of the study field. In this study, citation analysis is used as an analysis of all citations which indicate the type of information sources used by students and lecturers in writing the journal as a result of their research. The following research use two methods of analysis: Mind Mapping methods and SWOT Analysis. After conducting research and executing the research strategy, it will result in improving the reputation by increasing the number of citation and lecturer H-Index at Google Scholar which can automatically also increase the affiliations of authors at tertiary education in Google Scholar. Lecturers who have already verified authors in SINTA (Science and Technology Index) Ristekdikti can contribute in improving the rank and number of tertiary education scores on Ristekdikti Science and Technology Index (SINTA). This research produces a comprehensive and straightforward mathematical formula that can be used in understanding SINTA index calculation which will hence improve the enthusiasm of education community in pursuing research as a team as well as individually. Hopefully, with this research, students and lecturers are able to increase their citation and H-index on articles in publications so as to contribute in improving the reputation and quality of universities in the countries.